Data Service Outsourcing and Privacy Protection in Mobile Internet - Qin, Zhen; Zhou, Erqiang; Ding, Yi; Zhao, Yang; Deng, Fuhu; Xiong, Hu (IntechOpen, 2018)
Mobile internet data has the characteristics of large scale, variety of patterns, and complex association. On the one hand, it needs an efficient data processing model to provide support for data services, and, on the other hand, it needs certain computing resources to provide data security services. Due to the limited resources of mobile terminals, it is impossible to complete large-scale data computation and storage. However, outsourcing to third parties may cause risks in user privacy protection. This monograph focuses on key technologies of data service outsourcing and privacy protection, including the existing methods of data analysis and processing, fine-grained data access control through effective user privacy protection mechanisms, and data sharing in the mobile internet.